The Relationship Between Trait Emotional Intelligence and Burnout Among Workers in the Humanitarian Sector in Lebanon - Yassine, Raghida Abdallah; Antoun, Hiba; Nasr, Najoie (Journal of Organizational Psychology, 2023)
This study investigated the relationship between trait emotional intelligence and burnout among managers and non-managers in the humanitarian sector in Lebanon. We explored trait emotional intelligence as it relates to burnout while controlling for status (managerial and non-managerial) and working from home. The study’s results suggest a significant inverse relationship between the average score of trait emotional intelligence and burnout as total score. That is the higher the trait emotional intelligence score reported, the lower is the burnout score. Further analysis suggested that there is a significant relationship between trait emotional intelligence as a total score as well as the subscales burnout. This aligns with the studies on positive psychology and linkages between well-being and positive emotions. While controlling for employment status, results indicated that employment status (manager and non-manager) did not affect emotional exhaustion, which was unexpected. Finally, those working from home had higher levels of burnout than those who did not.